Legal protection for Indonesian workers in various countries Adenpati - Turnip, Agripa; Surbakti, Adenpati; Br Pandia, Jemita; Harahap, Rasyd; Wardana, Sitti; Tanjung, Indra U (Journal of Law Science, 2024)
The placement of migrant workers abroad is carried out by upholding human dignity, human rights, legal protection, equal employment opportunities and providing employment opportunities and employee training in accordance with national needs. However, violence often befalls Indonesian workers in their destination countries. So Indonesia created legislation in the form of protection for Indonesian workers, an international convention on protecting the rights of all migrant workers and their families which is often referred to as ICRMW. The ICRMW Agreement describes human rights contained in international law on economic, social and cultural rights and international law on civil and political rights specifically states how these different rights apply to different categories of migrant workers. Legal protection for the rights and obligations of migrant workers abroad is stated in a mutually agreed work relationship. Article 2 of Law Number 39 of 2004 regulates the principles of integration, harmony of rights, democracy, equality in society, justice, gender equality and anti-human trafficking. This is a form of legal protection for Indonesian workers